2018
DOI: 10.1093/femsle/fny023
|View full text |Cite
|
Sign up to set email alerts
|

The functional RNA cargo of bacterial membrane vesicles

Abstract: Bacteria secrete RNAs, some of which have effects on other cells and on other species as signalling RNAs. Prokaryotic membrane vesicles (MVs) contain a range of RNA types. The MV structure offers protection from degradation as well as receptors to facilitate delivery to target cells. Microscopic imaging and molecular biology analyses have provided evidence to demonstrate that bacterial MVs deliver their RNA into eukaryotic cells. Moreover, in some cases the RNA cargo is demonstrably functional and phenotypic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 102 publications
3
43
0
Order By: Relevance
“…That bacterial RNA and DNA can drive host immune responses and determining whether such responses are protective or detrimental to the host has been the subject of the majority of studies on immunomodulatory nucleic acids [1][2][3]5 . In comparison, fewer studies have examined how those immunomodulatory nucleic acids are secreted by bacteria in general-and by the extracellular human pathogen S. aureus in particular-and how they are transferred to host cells to eventually reach IFN signaling receptors 2,3,[18][19][20] . In conjunction with an increasing number of studies showing secretion of bacterial RNA and DNA via extracellular vesicle production [18][19][20] , we hypothesized that S. aureus secrete MVs containing bacterially-derived RNA and DNA molecules that can withstand nuclease degradation and be delivered into host cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…That bacterial RNA and DNA can drive host immune responses and determining whether such responses are protective or detrimental to the host has been the subject of the majority of studies on immunomodulatory nucleic acids [1][2][3]5 . In comparison, fewer studies have examined how those immunomodulatory nucleic acids are secreted by bacteria in general-and by the extracellular human pathogen S. aureus in particular-and how they are transferred to host cells to eventually reach IFN signaling receptors 2,3,[18][19][20] . In conjunction with an increasing number of studies showing secretion of bacterial RNA and DNA via extracellular vesicle production [18][19][20] , we hypothesized that S. aureus secrete MVs containing bacterially-derived RNA and DNA molecules that can withstand nuclease degradation and be delivered into host cells.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, fewer studies have examined how those immunomodulatory nucleic acids are secreted by bacteria in general-and by the extracellular human pathogen S. aureus in particular-and how they are transferred to host cells to eventually reach IFN signaling receptors 2,3,[18][19][20] . In conjunction with an increasing number of studies showing secretion of bacterial RNA and DNA via extracellular vesicle production [18][19][20] , we hypothesized that S. aureus secrete MVs containing bacterially-derived RNA and DNA molecules that can withstand nuclease degradation and be delivered into host cells. In this report we show for the first time that in cultured mouse macrophages, IFN-ß mRNA induction can be triggered by purified S. aureus MVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane vesicles consist of various types of lipids derived from cellular membranes along with numerous other biomolecules, such as membrane, periplasmic, and cytoplasmic proteins; DNA; RNA; and low molecular mass organic compounds that confer various biological functions (Brown et al, 2015;Schwechheimer and Kuehn, 2015;Dauros-Singorenko et al, 2018;Toyofuku et al, 2019). Recent studies have shown that there are different pathways of MV biogenesis, which produce different types of MVs (Toyofuku et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, OMVs contain a wide range of RNAs including ribosomal RNA (rRNA), transfer RNA (tRNA), messenger RNA (mRNA), and small non-coding RNA (sRNA) (Ghosal et al, 2015; Ho et al, 2015; Sjöström et al, 2015; Blenkiron et al, 2016; Choi et al, 2017; Soares et al, 2017; Dauros-Singorenko et al, 2018), which indicates that OMVs are important to study in the context of extracellular RNA communication.…”
Section: Introductionmentioning
confidence: 99%